Geometry of hypersurfaces of a quarter symmetric non metric connection in a quasi-Sasakian manifold - Rahman, Sh. (Carpathian Mathematical Publications, 2015)
The purpose of the paper is to study the notion of CR-submanifold and the existence of some structures on a hypersurface of a quarter symmetric non metric connection in a quasi-Sasakian manifold. We study the existence of a Kahler structure on M and the existence of a globally metric frame f-structure in sence of Goldberg S.I., Yano K. We discuss the integrability of distributions on M and geometry of their leaves. We have tries to relate this result with those before obtained by Goldberg V., Rosca R. devoted to Sasakian manifold and conformal connections.